Knowledge absorption capacity, learning and information technologies in organizations: state of the art and evolution of research - Abarca Sánchez, Yasser (2020)
This research aims to carry out the state of the art of the absorption capacity of knowledge, learning and information technologies (IT) in organizations; The references studied formulate relationships between the aforementioned variables in an incipient manner, so this article systematizes the information and proposes a graphical representation of complementarity between them. The methodology used is based on a systemic literary review, applying a bibliometric search of the variables using the Scopus and Science Direct databases by means of a documentary analysis, with an analytical-synthetic process based on the categorization of the capacity of absorption of knowledge, capacity for absorption of knowledge and learning and finally capacity for absorption of knowledge and information technologies, using criteria based on population, unit of analysis and year of publication for the final selection of articles. The result is the elaboration of graphical representations that outline the variables independently, as well as the relationship between them.